Using Dominance Analysis to Decompose Narcissism and Its Relation to Aggression and Externalizing Outcomes. (March 2019) - Vize, Colin E.; Collison, Katherine L.; Crowe, Michael L.; Campbell, W. Keith; Miller, Joshua D.; Lynam, Donald R.
Research on narcissism has shown it to be multidimensional construct. As such, the relations the larger construct bear with certain outcomes may mask heterogeneity apparent at the more basic trait level. This article used the Five Factor Narcissism Inventory, a Five-Factor Model–based measure of narcissism that allows for multiple levels of analysis, to examine the relative importance of narcissistic traits in relation to aggression, externalizing behavior, and self-esteem outcomes in two independent samples. The relative importance of the narcissism factors was determined through the use of dominance analysis—a relatively underused method for determining relative importance among a set of related predictors. The results showed that antagonism, compared with agentic extraversion and neuroticism, was the dominant predictor across all forms of aggressive behavior. Additional analyses showed that subscales within the broader factor of antagonism also showed differential importance relative to one another for certain aggression outcomes. The results are discussed in the context of the relation between narcissism and aggression and highlight the utility of using extensions of regression-based analyses to explore the heterogeneity within personality constructs.